2022
DOI: 10.1287/mnsc.2021.4140
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Feedback in Dynamic Crowdsourcing Contests: A Structural Empirical Analysis

Abstract: In this paper, we empirically examine the impact of performance feedback on the outcome of crowdsourcing contests. We develop a dynamic structural model to capture the economic processes that drive contest participants’ behavior and estimate the model using a detailed data set about real online logo design contests. Our rich model captures key features of the crowdsourcing context, including a large participant pool; entries by new participants throughout the contest; exploitation (revision of previous submiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 72 publications
2
7
0
Order By: Relevance
“…Therefore, making tentative submissions for preliminary feedback is indeed helpful for the enhancement of team performance. This is consistent with the simulation results in a previous study that platform feedback helps contest teams improve crowdsourcing outcome (Jiang et al. , 2022).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Therefore, making tentative submissions for preliminary feedback is indeed helpful for the enhancement of team performance. This is consistent with the simulation results in a previous study that platform feedback helps contest teams improve crowdsourcing outcome (Jiang et al. , 2022).…”
Section: Discussionsupporting
confidence: 93%
“…Based on such feedback as preliminary scores and rankings, the team can understand how well it is doing and improve the work accordingly. Previously, it was found that final scores helps team members understand their strengths and weaknesses for skill enhancement in future contests (Jiang et al, 2022). This study further posits that team outreach for platform feedback during a contest is conducive to eventual outcome.…”
Section: Research Modelsupporting
confidence: 56%
“…Scholars believe that static stock data cannot effectively reflect the changes in project design parameters over time. Therefore, the dynamics of the crowdsourcing contest process have received more attention [31]. Posts with timestamps show the knowledge-sharing trajectory of participants on the crowdsourcing work platform, making the knowledge-sharing trajectory a channel for platform participants to understand and influence each other.…”
Section: The Participation Behavior Of High-quality Solversmentioning
confidence: 99%
“…However, the focus of crowdsourcing contests is to guide more solvers to participate and obtain more high-quality solutions. Therefore, Jiang et al [31] simulate multiple stages of the crowdsourcing competition by building a dynamic structural model, and explore the impact of feedback on the solver's entry into the competition, exploration and development of new solutions. Similarly, Sanyal and Ye [30] also posit that feedback is a tool to dynamically improve the efficiency of public competitions.…”
Section: The Participation Behavior Of High-quality Solversmentioning
confidence: 99%
See 1 more Smart Citation